Rising trend of E-Commerce purchase by Indian Youths - Agrawal, Aditi (IJRDO - Journal of Business Management, 2015)
As technology continues to grow rapidly, E-Commerce players are adapting newer techniques tofacilitate efficient online selling and buying. More recently, with the introduction of flash salesand daily deals from various companies, E-Commerce has brought forward technnovation to theretail sector.Especially in developing countries like India, E-Commerce is on boom. Many big players are readyto invest in E-Commerce and are earning huge revenues. The major reason for growth of ECommerce in India is the astronomical population and youth. Youth possess a vital role in thegrowth of E-Commerce.The growth is driven by rapid technology adaptation led by the increasing use of devices such assmartphones and tablets and access to the internet through broadband 3G etc, which led to anincreased online consumer base.